Strategies to scale up the technical, allocative and economic efficiency of major millet growing farmers in India – A primal system approach - Kannan Thomas Felix; K.B. Ramappa; Padma Lakshmi Govindarajan (Environmental and Sustainability Indicators)
Millet farming, a sustainable and economically viable option for farmers, providing resilience against climate variability and market fluctuations. Despite the increasing significance of millets in agriculture, there is a notable research gap concerning the efficiency of their cultivation and its impact on input demand and costs. This study leverages data from CCPC for the AY 2021–22, focusing on major millets—Bajra, Jowar, and Ragi cultivated across various Indian states. The research aims to understand the technical, allocative, and economic inefficiencies in millet farming to enhance productivity and resource utilization. It is hypothesized that inefficiencies in millet cultivation significantly impact input demand and cultivation costs, and addressing these inefficiencies can lead to improved agricultural practices and yields. Employing primal Cobb-Douglas production function showed that human labor, seed quantity, and fertilizers positively impact millet cultivation. Technical inefficiency is a major issue with Bajra farmers in Gujarat, Haryana, Maharashtra, Rajasthan and Uttar Pradesh. For Jowar, farmers in Andhra Pradesh, Karnataka, Madhya Pradesh, Maharashtra, Rajasthan and Tamil Nadu are facing significant inefficiencies. In contrast, Karnataka and Odisha efficiently produce Ragi. Allocative inefficiency is noted in the over-utilization of animal and machine labor and fertilizers in Bajra cultivation, while these inputs are under-utilized in Jowar and Ragi cultivation. Both technical and allocative inefficiencies lead to increased input demand and higher cultivation costs across all three millets. The findings underscore the importance of state-specific strategies to address inefficiencies. These insights can guide policymakers in developing customized strategies to optimize millet cultivation, enhance yields and reduce costs.